SALURAN TERBUKA - Lutjito, Lutjito (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
ABSTRACT The sediment suspension phenomena have a close something to do with the watering field, the complexity of the existence of silt particles and clay in a fluida which are continuously interact and the turbulence which was happened has a specific characteristic. The problems on the sediment suspension flow on the open channel were approached with experimental method, i.e. by conducting a direct measurement of the sediment recirculating flume in Hydrology and Hydraulics Laboratory in PAU UGM. To measure the concentration profile of sediment suspension carriage, it is used optical silt measuring instruments type Foslim-probe tools, while to measure the flow speed profile, it is used electromagnetic flowmeter probe set type VM-201 H tools and vector calculate equipment type DV-101 tools. From the measurement of 10 series of uniform flow suspensed sediment, it shows that the integration constant value, Br, from logaritmic rule tends to be smaller compared with the integration constant value, Br for pure water, i.e. Br= 9. 110 +- 0.734. the integration constant value is affected by the sediment suspension concentration level which is showed by the fact that the raising concentration will cause the reduction of Br value. From the result of the computation, it shows that the coles wake parameterP for the suspensed uniform flow is P =0.085 with the constant value of Von Karman k =0.40 constant. It shows that te sediment suspension effect will cause the value of P will be more oppened, it is aggree with the result gained by Coleman (1986) which was said that the sediment suspension will cause the greater P value. Keywords: sediment suspension, uniform flow, open channel